Sams teach yourself LinkedIn in 10 minutes - Rutledge, Patrice-Anne (Sams teach yourself., 2012)
Sams Teach Yourself Linkedln® in 10 Minutes , Third Edition offers straightforward, practical answers when you need fast results. Learn everything you need to know to quickly and easily generate solid results on LinkedIn. Tips point out shortcuts and solutions Cautions help you avoid common pitfalls Notes provide additional information Plain English explains new terms and definitions 10 minutes is all you need to learn how to… Create a LinkedIn profile that generates results Find jobs, consulting opportunities, partners, and clients Enhance your visibility to an audience of millions Promote your business with a LinkedIn Company Page Develop a streamlined approach for managing contacts Customize LinkedIn for maximum effectiveness and productivity Use LinkedIn Answers and Groups for research and marketing Extend the power of LinkedIn with third-party applications and tools Give and receive professional recommendations Recruit job candidates Access LinkedIn from mobile devices Advertise on LinkedIn.